The use of foley catheter for treatment of unstable fracture zygomatic arch - De Queiroz, Sormani Bento Fernandes; De Lima, Valthierre Nunes; Aparecida Bazani, Paula Lorena [UNESP]; Bonardi, Joao Paulo; Magro-Filho, Osvaldo (Wolters Kluwer, 2016)
The isolated zygomatic arch fractures represent 21% of zygomatic-maxillary fractures and the falls is the main etiology. This type of fracture is easily reduced through several methods and the most used is the reduction through the surgical temporal approach of Gillies. The present patient illustrates the success treatment of a patient with isolated zygomatic arch fracture which a Foley catheter was used to stabilize the fracture reduction.
Keywords: Bone fracture; Facial injuries; Zygoma